Achieving Customer Satisfaction in Indomaret Bendul Sukatani Retail Business - Widiya Avianti (Journal of Business and Management Inaba, 2023)
This study aims to analyse the Promotion Program and Service Quality to Achieve Customer Satisfaction at Indomaret Bendul Sukatani. The data sources in this study are the results of observations, interviews, and documentation. Based on the research conducted, the following results and conclusions were obtained: The promotion process is carried out Continue by cashiers with limited human resources. Competitive prices offered in promotions are one of the more attractive to consumers in shopping. Promotional features in the form of the Indomaret Poinku application help increase consumer interest in shopping at Indomaret Bendul Sukatani. Factors that can be improved provide an understanding of the advantages of the Indomaret Poinku application purple program. Service quality is in accordance with the provisions of the Company, namely using the SOP 7 Service Vocabulary. Programmes that are already running on the Online and Offline shopping system can be improved to achieve fast and precise service to make it easier for consumers to shop quickly without waiting in long queues.